2020
DOI: 10.1055/s-0040-1710551
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral Antebrachial Neurocutaneous Flap: A Cadaveric Study and Clinical Applications

Abstract: Background The neurocutaneous flap is an axial pattern flap that receives a vascular supply from a vessel along its cutaneous nerve and has favorable outcomes when used for soft tissue reconstruction in the upper extremities. The neurocutaneous flap depends on the lateral antebrachial cutaneous nerve (LACN) and its retrograde-flow has been studied via cadaveric dissection. The aim of this study is to prove the vascularity of the lateral antebrachial neurocutaneous (LABN) flap. Methods The distally ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In this study, we did not strip the subcutaneous tissue between the donor site and primary wound, which would bring the following benefits: the destruction of normal tissue was reduced, the formation of the local scar was reduced, the congestion of the vascular pedicle between the donor site and the primary wound was reduced, and the morphological damage was avoided, so the long‐term benefits were clear. Previous studies have found that 20 the volume of the subcutaneous tunnel was 3 to 5 times that of the nutrient pedicle, and the stripping range was large, and the cost of injury was high. In this study, the ilioinguinal flap was used to repair the skin defect after excision of extensive Paget's disease of penis and scrotum.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we did not strip the subcutaneous tissue between the donor site and primary wound, which would bring the following benefits: the destruction of normal tissue was reduced, the formation of the local scar was reduced, the congestion of the vascular pedicle between the donor site and the primary wound was reduced, and the morphological damage was avoided, so the long‐term benefits were clear. Previous studies have found that 20 the volume of the subcutaneous tunnel was 3 to 5 times that of the nutrient pedicle, and the stripping range was large, and the cost of injury was high. In this study, the ilioinguinal flap was used to repair the skin defect after excision of extensive Paget's disease of penis and scrotum.…”
Section: Discussionmentioning
confidence: 98%
“…28 • For free-flap coverage, Kanit Sananpanich and Jirachart Kraisarin from Chiang Mai Hospital reported the descending geniculate artery-free flap 29 Thepparat Kanchanathepsak from Ramatibodi Hospital reported the lateral antebrachial neurocutaneous flap. 30 The resurfacing of thumb with neurovascular island flap from Pravit Kitidumrongsook 31 from Chulalongkorn hospital. Surasak Jitprapaikulsarn from buddhachinaraj hospital also reported the use of combined medial gastrocnemius and hemisoleous flap for tibial coverage.…”
Section: The Present Phase: 2000-to Datementioning
confidence: 99%